2014
DOI: 10.15376/biores.9.2.2396-2404
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Wood Pressure-treated with TiO2 Gel under Hydrothermal Conditions

Abstract: TiO 2 -treated acacia hybrid (Acacia mangium x auriculiformis) wood was fabricated by combined pressure-impregnation and hydrothermal posttreatment. The wettability and microstructure morphology, as well as the crystalline structure of the titanium dioxide (TiO 2 ) gels of the TiO 2 -treated wood, were studied. Contact angle measurements of the blank wood and the TiO 2 -treated wood indicated a significant increase in hydrophobicity, with contact angles of above 150° in treated samples. Furthermore, the water-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Many methods were applied to fabricate superhydrophobic coating based on this theory. In addition, there was much published research with remarkable results in the field of superhydrophobic coating for wood [11,12,32]. However, the durability of the superhydrophobic coating for wood is still the problem that needs to improve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods were applied to fabricate superhydrophobic coating based on this theory. In addition, there was much published research with remarkable results in the field of superhydrophobic coating for wood [11,12,32]. However, the durability of the superhydrophobic coating for wood is still the problem that needs to improve.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies have shown that coatings with hierarchical structures derived from surface roughness on the micrometer and nanometer scales, with low surface energy, can achieve superhydrophobicity and ultraviolet resistance [3,4,5,6,7,8]. In the case of wood nano-coating, there are several methods available, such as the sol-gel technique [9], the hydrothermal method [10,11], spray coating [12], layer-by-layer coating [13], solution-immersion [14], and cold plasma spraying [15].…”
Section: Introductionmentioning
confidence: 99%
“…These include nanosol treatment (Mahltig et al 2008;Xu et al 2010;Tshabalala et al 2011), the plasma-enhanced chemical vapor deposition of thin barrier films onto the wood surface (Denes et al 1999), and hydro/solvothermal treatment (Li et al 2010). Recently, there has been a renewed interest in the use of titanium dioxide nanostructures in combination with surface-active organic compounds to enhance the UV resistance and water repellence properties of wood surfaces (Wang et al 2011;Chu et al 2014;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Otras propiedades de los composites de madera y dióxido de titanio han sido estudiadas como la absorpción a la humedad o agua obteniendo una notable reducción de esta y con ello mejorando la durabilidad y estabilidad del material (ibídem et al, 2012 e ibídem et al, 2010). Otras propiedades que se obtienen relacionadas con la absorción son una menor mojabilidad, una mayor hidrofobicidad o un gran ángulo de contacto comparados con la madera sin tratar (Van Chu et al, 2014y Sun et al, 2011. Numerosas investigaciones (ibídem et al, 2014;ibídem et al, 2011;Li et al, 2010y Zheng et al, 2015 consiguen una estructura de dióxido de titanio usando métodos hidrotérmicos, pero, además, en los últimos años, varios estudios muestran que usando técnicas de spray para revestir de TiO 2 se obtienen muy buenos resultados de actividad fotocatalítica (Bordes et al, 2013), por lo que se usará este método para esta parte de la tesis.…”
Section: Selección De Materiales a Los Que Añadir Tiounclassified
“…- De Filpo et al, 2013;Miyafuji y Saka, 1997;Wang et al, 2012;Hübert et al, 2010;Van Chu et al, 2014;Sun et al, 2011;Li et al, 2010y Zheng et al, 2015 porque la capa llena parte de los poros de la madera natural. Por otro lado, el tratamiento térmico lo vuelve más áspero.…”
Section: Experimentación De Revestimiento De Tio 2 En Maderaunclassified